English Learning Management of Maritim Taruna in Seamanship Education and Training Center of Malahayati Aceh - Hartati, Diah Vitaloka; Yusrizal, Yusrizal Vitaloka; Bahrun, Bahrun Vitaloka (Jurnal Pendidikan Progresif, 2021)
This study aims to describe the planning, implementation and evaluation of Maritime English learning at BP2IP Malahayati. The technique of collecting data uses direct observation, in-depth interviews and documentation studies. Data analysis techniques through three stages, namely data reduction, data presentation and conclusion. The results of the study show that: (1) Planning for learning maritime English in BP2IP Malahayati consists of compiling syllabus in accordance with IMO Model Course 3.12 and compiling lesson plan (RPP) at the beginning of the semester; (2) The implementation of Maritime English learning at BP2IP Malahayati consists of initial activities, core activities delivered by learning materials and closing activities of the instructor giving assignments or quizzes to determine the extent to which students receive learning: (3) Evaluation of Maritime English Learning at BP2IP Malahayati carried out monitoring of students on 4 aspects, namely Listening, reading, speaking and writing. For the mid semester, midterms are given and at the end of the semester are given final semester examinations and practical exams.Keywords: learning management, english, seamanship education and training centerDOI: http://dx.doi.org/10.23960/jpp.v11.i3.202109